Synthesis of silver nanoparticles by using Aloe vera and Thuja orientalis leaves extract and their biological activity: a comprehensive review - Burange, Prashant J. (2023)
Nanotechnology's rapid development has been in great demand, particularly for silver nanoparticles, which are useful in a variety of industries including medicine, textiles, and home appliances. Silver nanoparticles are extremely essential due to their unique physicochemical and antibacterial properties, which can be used in a variety of applications. Green synthesis is an environmentally friendly alternative to conventional synthesis because it uses fewer chemical reagents and lowers temperature and pressure. Aloe vera and Thuja orientalis have a wide medical use because it contains a large number of compounds derived and was decided to use for the synthesis of nanoparticles.